Manajemen National Paralympic Committee (NPC) dalam pembinaan prestasi atlet penyandang disabilitas - Rahmawati, Dini; Wiyanto, Agus; Setyawan, Danang Aji (Edu Sportivo: Indonesian Journal of Physical Education, 2020)
The achievements made by persons with disabilities through sports are indeed quite interesting to study and observe, the purpose of this study is to analyze disability achievement management and supporting and inhibiting factors in the development of athletes with disabilities in the Kendal district NPC. The research design used is qualitative research, data collection techniques include: (1) observation, (2) interviews, (3) and documentation, with research subjects consisting of: (1) The Head of the Kendal Regency NPC, (2) Athlete Empowerment Section, (3) Sports Section, (4) Paralympic Athletes. The process of screening athletes in collaboration with sports teachers from special schools and teams from the NPC. Supervision is carried out by the National Paralympic Committee (NPC) from monitoring the condition of the athlete, the place where the athlete works and the athlete's family so that they understand that the athlete is performing. The conclusion in this study, NPC can increase organizational strengthening through coordination meetings, facilitate organization and implementation of guidance through grants from the Regional Government. Performance development for athletes with disabilities NPC conducts screening to special schools in order to find potential athletes, as well as to pay more attention to facilities and infrastructure to support performance development so that athletes with disabilities can achieve achievements.